Comparison of major population parameters of Brown hare (Lepus europaeus, Pallas 1758) in two hunting fields of the Great Hungarian Plain - Farkas, Péter; Majzinger, István; Kusza, Szilvia (Acta Agraria Debreceniensis, 2016)
Hungarian stock of game is not only part of our national treasure but also one of our domestic products and economic income. Not indifferent therefore the number and the state of health of our wildlife. Population decline of the Brown hare (Lepus europaeus, Pallas 1758) (one of our most important small game in Hungary) takes a long time. Demographic parameters of Brown hare was examined, particularly the factors affecting the decline of the species in Hungary. We took samples from typical habitats where the Brown hare could be found in relatively high density in our country. The article reports data of reproductive characteristics, diseases, parasites of Brown hare and other factors such as climatic and anthropogenic which could influence of the population dynamics. We mention sample collection and processing methods eg: population size estimates, examination of reproductive organs, the sex ratio and the age structure as well as the individual condition based on data of domestic and foreign authors and our partial results.